Summary of hospitalizations related to medicational poisoning groups in a cardiological and toxicological department from 04.2013 to 12.2021 - Zając, Marlena; Gruca, Dariusz; Wais, Marcin; Antoniak, Krzysztof; Tchórz, Michał (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Drug poisoning is one of the more common reasons for patients being hospitalized in toxicology wards. The wide availability and ease of obtaining a wide variety of drugs and supplements are the cause of adverse reactions associated with their use. Increasing life expectancy and emerging chronic diseases also require the use of sometimes many drugs to control people’s health. This can lead to poly-pragmasy, which is an undesirable condition and leads to poisoning. The purpose of our work is to demonstrate the most common causes of drug poisoning considering the criterion of division according to ICD-10. Brief description of the state of knowledge: Any preparation, drug, supplement can cause negative effects on the organism. This depends on the dose, improper use, or cross-reactions of the relevant substances. The study compiled statistics on the cause of hospitalization of drug-poisoned patients based on ICD-10. 5433 patients were included in the study. Conclusions: Our work shows that the most common causes of hospitalization due to drug poisoning are those caused by antiepileptic drugs, sedative-hypnotics and antiparkinsonism medications. The data compiled in this article agree with scientific reports from different countries compiling the most common reason for hospitalization related to drug poisoning.